Ideologi pada Kolom Opini Jawa Pos: Kajian Analisis Wacana: Ideology in the Opinion Column of Jawa Pos: A Discourse Analysis Study - Zakkiyah, Nur Naili; Ardhianti, Mimas (JBSI: Jurnal Bahasa dan Sastra Indonesia, 2025)
In the era of rapid information, opinion columns have become an important means of conveying individual or group opinions and ideologies. Ideology is combining and harmonisation of the way of thinking, feelings, and explanation of human attitudes towards life that suggests a leadership system to balance thinking. This column not only reflects the author's views but also contains an ideology that can influence the way readers think and behave. Language and ideology are closely related. The use of appropriate language by the author can influence, change, or even control the way readers understand and think about the ideas conveyed in their work, so that they can accept and believe in the author's ideology. This study was conducted to identify the relationship between text, social cognition, and social context in the opinion column in the Jawa Pos newspaper. This study utilises the critical discourse analysis method created by Teun A. Van Dijk and uses a qualitative descriptive approach. The data in this study are words, sentences, and paragraphs in the opinion column of the Jawa Pos newspaper. The data source used is the opinion column of the Jawa Pos newspaper for July-December 2024. Data collection uses documentation in the form of opinions from the Jawa Pos newspaper. The results of this study are that the text structure consists of several parts, such as macrostructure, superstructure, and microstructure. The structure of social cognition consists of several parts, such as person schema, self schema, role schema, and event schema, and the social context consists of two parts, namely practice and power.